KESETARAAN GENDER TERHADAP PEREMPUAN DALAM BIDANG PENDIDIKAN DI PERGURUAN TINGGI - Trisnawati, Opy; Widiansyah, Subhan (Universitas Tanjungpura, 2022)
Education is a right for everyone, both men and women, who have the right to get the same treatment and opportunities. The world of education should be a place to build good gender relations in social life. Gender equality means there are no different roles and positions between women and men in various aspects. Gender equality also refers to equal rights, responsibilities, and opportunities for women and men. Now gender equality has begun to be realized in the field of education. As in the case of learning, for example, every student in the class is free to access knowledge and express their opinion. No one takes precedence or ends, whether it is male or female. However, there are still some treatments that seem to discriminate against women, for example, in terms of friendship. When women try to mingle with men, they are still often sidelined because they are considered troublesome. This study aims to determine what conditions occur in universities responding to gender issues. The method used in this research is a qualitative method with a descriptive approach. . Data collection techniques used in this study include observation, interviews, and literature study by searching from various sources relevant to this research. The method used in selecting informants is using the purposive sampling technique.